MAIN ACTIVE COMPONENTS OF GOJI BERRY AND THEIR NUTRITIONAL IMPORTANCE – A REVIEW - Andrei Daniel TUDOR; Ciprian BOLOHAN; Valerica TUDOR; Răzvan Ionuț TEODORESCU (Journal of Applied Life Sciences and Environment)
The consumption of fruits, leaves, and roots of Lycium barbarum L. and Lycium chinense (Mill.) species has a long tradition, especially on the Asian continent, due to their health benefits. In recent decades, social and economic factors, along with scientific progress, have stimulated the expansion of the consumption and cultivation of goji plants on a global scale, but mostly in Western countries. The traditional therapeutic properties attributed to goji plants, scientifically demonstrated through clinical and pharmacological studies in vitro and in vivo, are due to a diversified content in antioxidants (polysaccharides, flavonoids, carotenoids, and antioxidant capacity). With the development of technological capabilities for the detection and extraction of biocompounds from plant resources (including from secondary metabolisms), the completeness of research on the beneficial and secondary effects of the use of these species in human nutrition has increased. In most of the published studies, the chemical profile of L. barbarum or L. chinense species was analysed in terms of the therapeutic benefits of the variety, the different plant components subjected to extraction, the prior processing of these components, the method of extraction of active biocompounds, and to some extent, the correlation of this profile with geographical origin. The objective of this study is to provide a comprehensive and updated summary on some chemical compounds with therapeutic effects from Lycium spp. plants, addressing the correlation of the phytochemical composition in relation to their cultivation area, in the perspective of identifying and creating new goji varieties with high adaptability to local pedoclimatic conditions.